2005
DOI: 10.1002/rcm.2180
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of inductively coupled plasma mass spectrometry based measurements: an application to the analysis of urinary barium, cesium, antimony and tungsten

Abstract: The wide use of barium (Ba), cesium (Cs), antimony (Sb) and tungsten (W) in many industrial and agricultural fields causes the increased release of these metals into the environment, laying the basis for health risk. To assess the exposure for the general population, the development of adequate and reliable analytical techniques becomes compulsory. This study refers to the quantification of urinary Ba, Cs, Sb and W levels by both quadrupole (Q) and sector field (SF) inductively coupled plasma mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…Urinary cesium levels reflect recent exposure. Two small studies of European populations reported urinary cesium levels similar to U.S. population results shown in this Report (Alimonti et al, 2005;. Using clinically submitted specimens, Komaromy-Hiller et al (2000) found urinary cesium levels that were slightly lower than those reported for the U.S. population.…”
Section: Urinary Cesiummentioning
confidence: 76%
“…Urinary cesium levels reflect recent exposure. Two small studies of European populations reported urinary cesium levels similar to U.S. population results shown in this Report (Alimonti et al, 2005;. Using clinically submitted specimens, Komaromy-Hiller et al (2000) found urinary cesium levels that were slightly lower than those reported for the U.S. population.…”
Section: Urinary Cesiummentioning
confidence: 76%
“…An analysis was performed in the trace elements laboratory at the Children's and Women's Health Centre of British Columbia in Vancouver. The technique used was previously described in detail (1). The analysis revealed that cesium appears to follow the laws of first-order elimination, two compartments being within the blood, one within erythrocytes and one within serum or The chloride salt of cesium, a group 1A element, is gaining popularity as an alternative treatment of advanced cancers.…”
Section: Case Presentationmentioning
confidence: 99%
“…Quelques domaines d'application en biologie clinique: Dans la famille des métaux alcalins, peu d'éléments trace nécessitent le recours à l'ICP-MS pour les analyses de biologie clinique. On peut citer de façon anecdotique les cas du rubidium (24) ou du césium (25) . Les autres éléments de cette famille sont plutôt investigués dans le cadre de la surveillance des expositions professionnelles ou environnementales pour le béryllium (28) ou dans un cadre médico-légal de diagnostic de noyade pour le strontium (29), sans poser de problèmes analytiques particuliers dans notre expérience.…”
Section: Difficultés Spécifiques Liées Aux Interférencesunclassified